KOYUN DALAK DOKU ARGİNAZININ BAZI KİNETİK ÖZELLİKLERİ - KANDEMİR, FATİH MEHMET (Fırat Üniveristesi, 2009)
Bu çalışma ile koyun dalak doku arginazının bazı kinetik özellikleri ilk kez laboratuarımızda optimize edilmiştir.Koyun dalak doku arginazı için preinkübasyon ısısı 58 °C, preinkübasyon zamanı 13 dakika, inkübasyon zamanı 10 dakika ve optimum pH 9.5 olarak saptanmıştır. Enzim en yüksek aktiviteyi 2 mM MnCl2 konsantrasyonunda vermiştir. Sonuç olarak enzimin aktivasyonu için Mn+2 iyonlarının ve 58 °C' de preinkübasyonun gerekli olduğu tespit edilmiştir. Koyun dalak doku arginazının L-arginine karşı olan Km' i 6 mM olarak saptanmıştır.L- ornitin ve L- lizin gibi L- amino asitler enzim aktivitesini non-kompetetif inhibe etmiştir. Guanidino bileşiklerinden L- kanavanin enzimi non-kompetetif olarak inhibe etmektedir.EDTA, NEM, p-CMBA ve metilen mavisinin koyun dalak doku arginaz aktivitesini önemli ölçüde düşürdüğü gözlenmiştir. EDTA enzimi kompetetif inhibe ederken diğerleri non-kompetetif inhibe etmektedir. Koyun dalak doku arginazının yaklaşık % 50' sinin hücre çekirdeğinde, diğer % 50' sinin de sitoplazmada lokalize olduğu tesbit edilmiştir.Farklı ışık koşullarında metilen mavisinin arginaz aktivitesi üzerine olan etkisi araştırılarak metilen mavisinin, ışığın ve MnCl2' ün koyun dalak doku arginazının fotoinaktivasyonuna olan etkileri saptanmıştır.Anahtar Kelimeler: Arginaz , kinetik özellikler, koyun dalak dokusu.

In this study, some kinetic properties of arginase in the sheep spleen tissue was been optimized at first time in our laboratory.Its was found to be preincubation temperature 58 °C, preincubation period 13 minutes, incubation period 10 minutes and optimum pH 9.5 for sheep spleen tıssues. Enzyme achieved its highest activity at 2.25 mM MnCl2 concentration. Consequently, ıt was determined that Mn+2 ions and preincubation at 58 °C were essential for the activation of the enzyme. Km of arginase in sheep spleen tissue for arginine were determined tobe 6 mM.L- amino acids, such as L- ornithine and L- lysine inhibited the enzyme activity non-competitively. Among guanidino compounds L- canavanine inhibited the enzyme non-competitively.EDTA, NEM, p-CMBA and methylene blue were reduced arginase activity of the sheep spleen tissue. The enzyme activity was inhibited competitively by EDTA and non-competitively by the others. It was determined that approximately 50% percent of arginase in sheep spleen tissue was localized in the cell nucleus and the remaining one in the cell cytoplasm.It was investigated that methylene blue was effected on the arginase activation in different light and were determined that methylene blue, light and MnCl2 effect photoinactivation of arginase in the sheep spleen tissue.Key Words: Arginase, kinetic properties, sheep spleen tissue.
Some kinetic properties of arginase in the sheep spleen tissue
Keywords: Biyokimya